Development of Management Information System Reservations Using Simple Multi-Attribute Rating Technique (SMART) Based on Android Mobile Applications - Ahmad Habib; Ardy Januantoro; Okky Candra Srimarsono (Soegijapranata Catholic University, 2021)
In the information age, technology has become one of the things that are growing more rapidly, one of the technologies is the internet. From the use of the internet, it can also be used by sales that have Android mobile-based bread ordering information systems. By only using a cell phone, system users can order bread. This can be a tool in the special community in ordering bread. As with computers, mobile phones can also install a variety of software or software that they want. Besides, android phones can also be used for transactions. Like making a bread order transactions through an android phone. The stages that will be carried out by the author for the application development process include analysis and needs, application design, and application interface design, so that the application is made easy to use. The ordering system designed can make it easier for admin to view order details, check stock, manage customer data by using a database as a storage medium, and can also provide customers to buy stock of bakery goods available at these outlets to provide accurate information. The SMART method has been proven to be implemented in searches based on user preferences, and gives different results if the value of the criteria entered is different. However, conventional search methods are still provided in addition to searching for goods using the SMART Method.